A companion to Greek literature - Hose, Martin; Schenker, David J. (Chichester, West Sussex : John Wiley and Sons, Inc., 2015)
A Companion to Greek Literature presents a comprehensive introduction to the wide range of texts and literary forms produced in the Greek language over the course of a millennium beginning from the 6th century BCE up to the early years of the Byzantine Empire. Features contributions from a wide range of established experts and emerging scholars of Greek literature Offers comprehensive coverage of the many genres and literary forms produced by the ancient Greeks-including epic and lyric poetry, oratory, historiography, biography, philosophy, the novel, and technical literature Includes readin.
Introduction / Martin Hose, David Schenker -- Production and Transmission. Mechanics and Means of Production in Antiquity / Lucio Del Corso -- A Wound, not a World / Richard H Armstrong -- Greek Literature as a Dynamic System. Orality and Literacy / Steve Reece -- Literature in the Archaic Age / Timothy Power -- Literature in the Classical Age of Greece / James McGlew -- Literature in the Hellenistic World / Anatole Mori -- Greek Literature in the Roman World / Jason König -- The Encounter with Christianity / Jan Stenger -- Genres. Greek Epic / Hanna M Roisman -- Lyric / James Bradley Wells -- The Ethics of Greek Drama / Richard Rader -- Epigram and Minor Genres / Regina Hoschele -- Oratory / Mike Edwards -- Historiography and Biography / Antonis Tsakmakis -- Philosophical Writing / Martin Hose -- The Novel / Stefan Tilg -- Technical Literature / Thorsten Fogen -- The Players. The Creators of Literature / Mary Lefkowitz -- Users of Literature / Rene Nunlist -- Sponsors and Enemies of Literature / David Schenker -- The Places. Places of Production / Martin Hose -- Places of Presentation / Manuel Baumbach -- Topos and Topoi / Suzanne Said -- Literature and knowledge. Literature and Truth / Martin Hose -- Knowledge of Self / Daniela Dueck -- Explicit Knowledge / Markus Asper -- Implicit Knowledge / David Konstan -- Preserved Knowledge / Markus Dubischar -- Literature and Aesthetics. The Language of Greek Literature / Andreas Willi -- Poetic Devices in Greek Literature / Nicholas Baechle -- The Function of Literature / Victoria Wohl -- The Reception of Greek Literature. Trends in Greek Literature in the Contemporary Academy / Emily Wilson -- The Reception of Ancient Greek Literature and Western Identity / Edith Hall.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Greek literature -- History and criticism; Greek literature -- History and criticism; Greek literature; Literature; LITERARY CRITICISM -- Ancient & Classical; Greek literature; Electronic books; Criticism, interpretation, etc